ANALYSIS OF SCIENCE LITERACY IN SCIENCE TEXTBOOKS FOR JUNIOR HIGH SCHOOL BASED ON THE REVISED 2013 CURRICULUM IN WEST JAKARTA - Fakhri, Fakhri; Herlanti, Yanti (Universitas Tanjungpura, 2025)
Textbooks play an important role in the learning process, curriculum, and instructional methods, especially in developing countries. Text to translate: Textbooks are used as the main source to improve students' abilities in terms of science literacy. Students' science literacy skills are still below the PISA (Programme for International Student Assessment) standards. This study aims to analyze the scope of science literacy contained in the revised 2013 Curriculum Junior High School Science textbooks. The sample used is the SMP science textbooks from junior high schools in West Jakarta. The sampling technique in this study is purposive sampling, while the method used is descriptive, specifically document analysis in the form of textbooks. The instrument used to analyze the science textbooks is an observation sheet containing categories of science literacy. The results of the analysis on the Grade VIII SMP Science textbook of the 2013 Revised Curriculum show the proportion of science literacy with a percentage of 72.58% Knowledge of Science, 21.04% Investigative Nature of Science, 4.02% Science as a Way of Thinking, and 2.36% Interaction of Science, Technology, and Society.